FRI0193 ULTRASONOGRAPHY IN THE DIAGNOSIS OF GIANT CELL ARTERITIS. (2nd June 2020) - Jese, R.; Rotar, Z.; Tomsic, M.; Hocevar, A.
Abstract : Background: Objectives: To evaluate the frequency of cranial and aortic arch artery involvement in GCA using color Doppler ultrasonography (CDS). Methods: We performed CDS of cranial and aortic arch arteries in 248 incipient, clinically diagnosed, GCA patients (64.9% females, median (IQR) age 75 (67-80) years) between October 2013 and September 2019, using a Philips IU22 with 5–17.5 MHz linear probe or Philips Epiq 7 with 5–18.5 MHz linear probe. Temporal, facial, occipital, carotid, vertebral, subclavian, and axillary arteries were examined bilaterally. A halo with positive compression sign was considered a positive finding. Additionally, the thickness of intima-media complex (IMT) of individual vessel was measured, and compared to the IMT of 97 consecutive suspected GCA cases (60.8% females median (IQR) age 74 (65-81) years), in whom GCA was excluded, that served as a control group. Results: The CDS was positive in 244 (98.4%) patients in at least one of the examined arteries. Temporal arteries were most commonly affected, and were involved in 192 (77.4%) patients, followed by facial and occipital arteries, involved in 122 (49.2) and 72 (29.0%) patients, respectively. Extracranial large vessel involvement (LVV) was found in 87 (35.1%) patients (32 patients had isolated LVV, and 55 concomitant cranial and LVV artery involvement). Among the 161 patients without LVV, 12 (4.8% of the studied cohort) had involvement of cranial arteries other than temporal arteries (we found facial and occipital artery involvement in 11 and 3 patients, respectively). Table 1 shows the frequency of individual vessel involvement in GCA, and the IMT of CDS inflamed and non-inflamed arteries in GCA, and in controls. Conclusion: CDS of seven preselected cranial and aortic arch arteries provides a high diagnostic yield in GCA. Disclosure of Interests: Rok Jese: None declared, Ziga Rotar Consultant of: Speaker and consulting fees from Abbvie, Amgen, Biogen, Eli Lilly, Medis, MSD, Novartis, Pfizer, Roche, Sanofi., Speakers bureau: Speaker and consulting fees from Abbvie, Amgen, Biogen, Eli Lilly, Medis, MSD, Novartis, Pfizer, Roche, Sanofi., Matija Tomsic: None declared, ALOJZIJA HOCEVAR: None declared